Big Russ and me father and son, lessons of life - Russert, Tim 1950-2008 (Miramax Books, 2004)
The author offers a memoir of life with his father, a proud World War II veteran, describing growing up in 1950s Buffalo, the influence of his Catholic upbringing, and the importance of hard work, responsibility, and patriotism.